2017
DOI: 10.1007/s10902-017-9893-7
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude, Psychopathology and Subjective Well-Being: Results from a 7.5-Month Prospective General Population Study

Abstract: Gratitude is considered an important source of human strength in achieving and maintaining good mental health. Although complete mental health encompasses the absence of psychopathology and the presence of subjective well-being, no studies to date have examined relations between gratitude and both mental health dimensions together. Moreover, most studies focused on specific samples with a restricted demographic range. Our study, therefore, examined (a) demographic variability in the grateful trait, and (b) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 66 publications
(101 reference statements)
4
25
0
4
Order By: Relevance
“…It was found that resilience, affective empathy, and gender were all significant predictors of gratitude. This result is consistent with previous research (Dwiwardani et al 2014;McCullough et al 2004), and suggests that women might possess a social and emotional advantage over men in that they are more likely to experience and express gratitude (Jans-Beken, Lataster, Peels, Lechner, & Jacobs, 2017). The present results also support the hypothesis that gratitude serves as a virtuous behavior in that it is expressed in relationships, and may stem from the ability to stay emotionally strong amidst adversity or to cope effectively with stressors and difficult circumstances (Dwiwardani et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was found that resilience, affective empathy, and gender were all significant predictors of gratitude. This result is consistent with previous research (Dwiwardani et al 2014;McCullough et al 2004), and suggests that women might possess a social and emotional advantage over men in that they are more likely to experience and express gratitude (Jans-Beken, Lataster, Peels, Lechner, & Jacobs, 2017). The present results also support the hypothesis that gratitude serves as a virtuous behavior in that it is expressed in relationships, and may stem from the ability to stay emotionally strong amidst adversity or to cope effectively with stressors and difficult circumstances (Dwiwardani et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, the older person becomes, the more grateful they are. This effect was also found in other studies (Jans-Beken et al 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Model three tested a mediation with two mediators. The study controlled for the demographic variables age, gender (0 ¼ male, 1 ¼ female) and educational level (0 ¼ low education, 1 ¼ high education) in all models as previous studies showed possible associations between age, gender and educational differences in the experience of loneliness (Chukwuorji, Amazue, & Ekeh, 2017;Hawkley & Kocherginsky, 2018) and gratitude (Jans-Beken et al, 2017). As advised by Yzerbyt, Muller, Batailler, and Judd (2018), bootstrapping was performed with 50,000 resamples.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the focus is on the association between trait gratitude and loneliness, and the effects of psychological flexibility and engaged living as underlying mechanisms in the association between trait gratitude and loneliness in adults of 40 years and older. These mechanisms have CONTACT Jennifer Reijnders jennifer.reijnders@ou.nl shown to be beneficial for increased physical and mental health and decreased psychopathological problems (Jans-Beken, Lataster, Peels, Lechner, & Jacobs, 2017;Kashdan & Rottenberg, 2010;Trompetter et al, 2013). This study aims to reveal more knowledge about the possible role of trait gratitude, psychological flexibility and engaged living in relation to loneliness with possible implications for developing interventions to reduce loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…Desde la perspectiva de la salud mental, se ha asociado a resultados como mayores niveles de emociones positivas, satisfacción vital y conductas prosociales 7,31 y a menores niveles de estrés en embarazadas 32 , sintomatología depresiva 8,31,33 , angustia ante la muerte 34 , distorsiones cognitivas asociadas al peso y a la imagen corporal 35 , sintomatología asociada al estrés 36 , psicopatología en general 37 , sintomatología ansiosa 38 , consumo de sustancias 39 y suicidalidad 40 . Además, se ha asociado a una mejor calidad de vida y a una mayor adherencia a tratamiento 41 .…”
Section: Potenciales Beneficios De La Gratitud En Saludunclassified